POLA PENGASUHAN TARUNA BERBASIS KETELADANAN PADA TARUNA POLITEKNIK PELAYARAN SUMATERA BARAT - Riyanto, Budi; Rivolindo, Rivolindo (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
West Sumatra Shipping Polytechnic as a vocational university becomes the organizer of Shipping Education and Training to realize the Superior, Professional, Value and Character of Human Resources in the Shipping Field of its students. This educational process starts from the basic education period that must be passed by all cadets. At this time, changes in attitude, mentality and personality are expected. To see this, the general description of the care process and the application of exemplary based learning. The study was conducted using qualitative methods accompanied by research data searches through observation and interviews. The results showed that the care process had a significant influence on the success of the parenting process itself. Exemplary pattern of parenting by prioritizing the learning system has been running during the basic education period of the West Sumatra Shipping Polytechnic